RESPONS PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP PEMBERIAN KOMBINASI PUPUK KOMPOS KIRINYUH (Chromolaena odorata) DAN NPKMg (15:15:6:4) PADA BERBAGAI DOSIS DI PEMBIBITAN UTAMA - Maryani, Anis Tatik; Fathia, Nyimas Myrna Elsa; Wahyuni, Wahyuni (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2025)
ABSTRACT Palm oil productivity in Jambi Province in 2023 has decreased.. This research aims to study the growth response of oil palm seeds (Elaeis guineensis jacq.) to the combination of kirinyuh compost fertilizer (Chromolaena odorata) and NPKMg fertilizer (15:15:6:4) at various doses in the main nursery. This research was carried out at the Teaching and Research Farm of the Faculty of Agriculture, Jambi University. The research was carried out for 3 months, using a Complete Random Design (RAL) namely k0 : Without kirinyuh compost fertilizer + 100 % NPKMg fertilizer (15:15:6:4) k1 : Kirinyuh compost 100 grams/polybag + 50 % NPKMg fertilizer (15:15:6:4) k2 : Kirinyuh compost fertilizer 150 grams/polybag + 50 % NPKMg fertilizer (15:15:6:4) k3 : Kirinyuh compost 200 grams/polybag + 50 % NPKMg Fertilizer (15:15:6:4) k4 : Kirinyuh compost fertilizer 250 grams/polybag + 50 % NPKMg (15:15:6:4) This experiment consists of 5 treatments with 4 repetitions so that 20 experimental units are obtained. Each experimental unit consists of 3 plants so that there are a total of 60 plants. The data is statistically analyzed using Anova and if there is a real effect, it is continued with the DMRT test at the level of α = 5 %. The results of the study concluded that the application of kirinyuh compost has a real effect on the variable of seed height, number of leaves, total leaf area, and has a very real effect on the diameter of the lump, the dry weight of the head and the dry weight of the root, the seed quality index. And the dose of 200 grams/polybag + 50% NPKMg Fertilizer shows the best dose for the growth of oil palm seeds. Keywords : Palm Oil, Kirinyuh Compost Fertilizer, NPKMg Fertilizer